FETISISME KOMODITI MELALUI PROSES KREATIF 347 - Wajar Bimantoro (Jurnal Dimensi Seni Rupa dan Desain, 2006)
AbstractComodity Fethishism which is related to creative process of 347 trademark. What is the relationship between them? Are they support each other , or is it just to make it sounds modern, or are they  do not have any relationship  at all? It moves from impish creativity to become imphisness that result cretaon will unlimited values. The form of efforts are also structurized and order , from the founder, owner, designer-who are also functioned as the creative team, to its proffesional employees. IN this case, the writer tries to simply describe how a 347  trademark, that works on selling fashion and accesories of youngsters in Bandung city might become the commodity that has mysterious power ( unique selling point ) among the youngsters ( not only in Bandung city, but also all the way to Jakarta) AbstrakFetisisme KOmoditi yang dihubungkan dengan proses kreatif pada merek dagang 347. Apa hubungan keduanya, apakah saling mendukung atau hanya sekedar istilah agar terlihat beken, atau memang tidak ada hubungannya sama sekali? Tulisan ini mencoba menjabarkan secara sederhana bagaimana suatu merek dagang 347 , yang bergerak dalam bidang penjualan fashion dan asesories anak muda di kota Bandung dapat menjadi komoditi yang mempunyai kekuatan yang misterius ( unique selling point) di kalangan anak muda